Indigenous parents and child welfare: Mistrust, epistemic injustice, and training - Leckey, Robert; Schmieder-Gropen, Raphael; Nnebe, Chukwubuikem; Clouthier, Miriam (Social & Legal Studies, 2022)
The settler state's taking of Indigenous children into care disrupts their communities and continues destructive, assimilationist policies. This article presents the perceptions of lawyers, social workers and judges of how Indigenous parents experience child welfare in Quebec. Our participants characterized those experiences negatively. Barriers of language and culture as well as mistrust impede meaningful participation. Parents experience epistemic injustice, wronged in their capacity as knowers. Mistrust also hampers efforts to include Indigenous workers in the system. Emphasizing state workers’ ignorance of Indigenous family practices and the harms of settler colonialism, participants called for greater training. But critical literature on professional education signals the limits of such training to change institutions. Our findings reinforce the jurisdictional calls away from improving the system towards empowering Indigenous peoples to run services of child welfare. The patterns detected and theoretical resources used are relevant to researchers of other institutions that interact with vulnerable populations.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; australie; canada; care; cours; cycles supérieurs; discipline; droit; enfants autochtones; fem9000; injustice; inégalités; nouvelle-zélande; océanie; politique assimilationniste; périodes historiques; racisme; régions géographiques; santé; science politique et droit; sciences humaines; sciences sociales; système colonial; systèmes d'oppressions; thématiques; violences; états coloniaux

Justice and the politics of difference - Young, Iris Marion; Allen, Danielle S. (Princeton University Press, 2022)
"In this classic work of feminist political thought, Iris Marion Young challenges the prevailing reduction of social justice to distributive justice. The starting point for her critique is the experience and concerns of the new social movements that were created by marginal and excluded groups, including women, African Americans, and American Indians, as well as gays and lesbians. Young argues that by assuming a homogeneous public, democratic theorists fail to consider institutional arrangements for including people not culturally identified with white European male norms. Consequently, theorists do not adequately address the problems of an inclusive participatory framework. Basing her vision of the good society on the culturally plural networks of contemporary urban life, Young makes the case that normative theory and public policy should undermine group-based oppression by affirming rather than suppressing social group differences"
Section: x, 286 pages ; 24 cm.
Keywords: 2000 à aujourd'hui; 2010-2019; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; discours dominant; fem9000; inégalités; justice sociale; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis

Nous sommes tous des féministes - Adichie, Chimamanda Ngozi (Gallimard, 2020)
Dans le premier texte, à l'origine un discours prononcé en 2012 dans le cadre d'un programme dédié à l'essor du continent africain, l'écrivaine nigériane aborde avec lucidité et humour le sujet du féminisme. A travers des anecdotes issues de sa vie quotidienne, au Nigeria comme aux Etats-Unis, elle évoque les questions de l'inégalité des sexes et de l'image de soi des femmes.
Keywords: afrique; afro-féminisme; amériques; approches et analyses; cours; cycles supérieurs; droits des femmes*; fem7000; féminismes noirs; inégalités; lit3220; nigeria; premier cycle; rapports sociaux de sexe; régions géographiques; systèmes d'oppressions; thématiques; écriture des femmes*; états-unis

Metaepistemic Injustice and Intellectual Disability: a Pluralist Account of Epistemic Agency - Catala, Amandine (Ethical Theory and Moral Practice, 2020)
The literature on epistemic injustice currently displays a logocentric or propositional bias that excludes people with intellectual disabilities from the scope of epistemic agency and the demands of epistemic justice. This paper develops an account of epistemic agency and injustice that is inclusive of both people with and people without intellectual disabilities. I begin by specifying the hitherto undertheorized notion of epistemic agency. I develop a broader, pluralist account of epistemic agency, which relies on a conception of knowledge that accounts not only for propositional knowing, but also for other types of knowing that have been largely neglected in debates on epistemic injustice and agency. Based on this pluralist account of epistemic agency, I then show that people with intellectual disabilities qualify as epistemic agents and therefore as subjects of epistemic justice. Finally, I argue that this pluralist account of epistemic agency pushes us to revisit the current conception of epistemic injustice and to expand its taxonomy in two important ways.
Keywords: EDI; agentivité épistémique; approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; handicap intellectuel; injustices épistémiques; inégalités; justice sociale; justice épistémique; philosophie; savoir propositionnel; sciences humaines; systèmes d'oppressions; taxonomie des savoirs; thématiques; violences; éthique

Microaggressions and philosophy - Freeman, Lauren; Weekes Schroer, Jeanine (Routledge, 2020)
"This is one of the first books to offer a comprehensive philosophical treatment of microaggressions. Its aims are to provide an intersectional analysis of microaggressions that cuts across multiple groups and dimensions of oppression and marginalization, and to engage a variety of perspectives that have been sidelined within the discipline of philosophy. The volume gathers a diverse group of contributors: philosophers of color, philosophers with disabilities, philosophers of various nationalities and ethnicities, and philosophers of several genders and gender identities. Their unique frames of analysis articulate both how the concept of microaggressions can be used to clarify and sharpen our understanding of subtler aspects of oppression and how analysis, expansion, and reconceiving the notion of a microaggression can deepen and extend its explanatory power. The essays in the volume are divided into four thematic parts. The essays in Part I seek to defend microaggressions from common critiques and to explain their impact beyond the context of college students. In Part II the contributors set forth a framework for legitimizing microaggressions research that takes into account issues of measurement, scale, and replication. Part III explores the harms of microaggressions. The chapters show how small slights can accumulate to produce significant harm at the macro level, demonstrate how microaggressions contribute to epistemic harm, and establish novel understandings of racial and accent-triggered microaggressions. Finally, Part IV addresses issues of disability and ableism within the context of microaggressions. It includes commentary on transgender athletes, disciplinary techniques for bodily nonconformity, ableist exceptionalism, and deafness. Microaggressions and Philosophy features cutting-edge research on an important topic that will appeal to a wide range of students and scholars across disciplines. It includes perspectives from philosophy of psychology, empirically informed philosophy, feminist philosophy, critical race theory, disability theory, philosophy of language, philosophy of science, and social and political philosophy"– Provided by publisher.
Keywords: EDI; approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; histoire et politique; hétérosexisme; intersectionnalité; inégalités; micro-agression; philosophie; psychologie; racisme; sciences humaines; sexisme; sofia; systèmes d'oppressions; thématiques; transphobie; violences; études critiques de la race; études critiques du handicap

On Epistemic Appropriation - Davis, Emmalon (Ethics, 2018)
In this article, I offer an account of an unjust epistemic practice―namely, epistemic appropriation―that harms marginalized knowers through the course of conceptual dissemination and intercommunal uptake. The harm of epistemic appropriation is twofold. First, while epistemic resources developed within the margins gain uptake with dominant audiences, those resources are overtly detached from the marginalized knowers responsible for their production. Second, epistemic resources developed within, but detached from, the margins are utilized in dominant discourses in ways that disproportionately benefit the powerful.
Keywords: approches et analyses; appropriation épistémique; cours; cycles supérieurs; discipline; discours dominant; droits des personnes; fem9000; injustices épistémiques; inégalités; philosophie; privilèges; rapports de pouvoir; savoirs des marges; sciences humaines; systèmes d'oppressions; thématiques; violences; éthique

Credibility Excess and the Social Imaginary in Cases of Sexual Assault - Yap, Audrey S (Feminist Philosophy Quarterly, 2017)
This paper will connect literature on epistemic injustice with literature on victims and perpetrators, to argue that in addition to considering the credibility deficit suffered by many victims, we should also consider the credibility excess accorded to many perpetrators. Epistemic injustice, as discussed by Miranda Fricker, considers ways in which someone might be wronged in their capacity as a knower. Testimonial injustice occurs when there is a credibility deficit as a result of identity-prejudicial stereotypes. However, criticisms of Fricker have pointed out that credibility is part of a more complex system that includes both deficits and excesses. I will use these points to argue that we should look closer at sources of credibility excess in cases of sexual assault. This means that in addition to considering sources of victim blaming by looking at ways in which “ideal” victims are constructed, we also need to consider ways in which “ideal” perpetrators are constructed.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem9000; injustices testimoniales; injustices épistémiques; inégalités; philosophie; philosophie féministe; privilèges; racisme; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; violences sexistes et sexuelles; éxcès de crédibilité

Epistemic Exploitation - Berenstain, Nora (Ergo, an Open Access Journal of Philosophy, 2016)
Epistemic exploitation occurs when privileged persons compel marginalized persons to educate them about the nature of their oppression. I argue that epistemic exploitation is marked by unrecognized, uncompensated, emotionally taxing, coerced epistemic labor. The coercive and exploitative aspects of the phenomenon are exemplified by the unpaid nature of the educational labor and its associated opportunity costs, the double bind that marginalized persons must navigate when faced with the demand to educate, and the need for additional labor created by the default skepticism of the privileged. I explore the connections between epistemic exploitation and the two varieties of epistemic injustice that Fricker (2007) identifies, testimonial and hermeneutical injustice. I situate epistemic exploitation within Dotson’s (2012; 2014) framework of epistemic oppression, and I address the role that epistemic exploitation plays in maintaining active ignorance and upholding dominant epistemic frameworks.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; discours dominant; exploitation épistémique; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; inégalités; oppression épistémique; philosophie; privilèges; sciences humaines; systèmes d'oppressions; thématiques; travail; violences; éthique

Typecasts, Tokens, and Spokespersons: A Case for Credibility Excess as Testimonial Injustice - Davis, Emmalon (Hypatia, 2016)
Miranda Fricker maintains that testimonial injustice is a matter of credibility deficit, not excess. In this article, I argue that this restricted characterízation of testimonial injustice is too narrow. I introduce a type of identity-prejudicial credibility excess that harms its targets qua knowers and transmitters of knowledge. I show how positive stereotyping and prejudicially inflated credibility assessments contribute to the continued epistemic oppression of marginalized knowers. In particular, I examine harms such as typecasting, compulsory representation, and epistemic exploitation and consider what hearers are obligated to do in response to these injustices. I argue that because epistemic harms to rnarginatized knowers also arise from prejudicially inflated assessments of their credibility, the virtue of testimonial justice must be revised to remedy them.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; droits des personnes; excès de crédibilité; fem9000; fricker; injustices testimoniales; inégalités; justice sociale; philosophie; privilèges; sciences humaines; systèmes d'oppressions; thématiques; violences; éthique

Teaching community: A pedagogy of hope. - hooks, bell (Taylor and Francis, 2013)
Il y a dix ans, bell hooks étonnait les lecteurices avec Enseigner à transgresser : l'éducation comme pratique de la liberté . Vient maintenant Communauté d'enseignement : une pédagogie de l'espoir - une œuvre puissante et visionnaire qui enrichira notre enseignement et nos vies. Combinant une réflexion critique sur l'éducation avec des récits autobiographiques, hooks invite les lecteurices à étendre le discours sur la race, le sexe, la classe et la nationalité au-delà de la salle de classe dans des situations d'apprentissage quotidiennes. L'enseignement, explique-t-elle, peut avoir lieu n'importe où, n'importe quand - pas seulement dans les salles de classe des collèges, mais dans les églises, les librairies, les maisons où les gens se réunissent pour partager des idées qui affectent leur vie quotidienne. Dans Teaching Community, bell hooks cherche à théoriser à partir de la place du positif, en regardant ce qui fonctionne. Écrivant sur les luttes pour mettre fin au racisme et à la suprématie blanche, elle fait valoir que "personne ne naît raciste. Tout le monde fait un choix". Communauté d'enseignement nous explique comment nous pouvons choisir de mettre fin au racisme et de créer une communauté bien-aimée. hooks se penche sur de nombreux problèmes, parmi lesquels la spiritualité en classe, les Blancs cherchant à mettre fin au racisme et les relations érotiques entre professeur.e.s et étudiant.e.s. L'esprit, la lutte, le service, l'amour, les idéaux de connaissance partagée et d'apprentissage partagé - ces valeurs motivent un changement social progressif. Les enseignant.e.s visionnaires savent que l'éducation démocratique ne peut jamais se limiter à une salle de classe. L'enseignement - si souvent sous-estimé dans notre société - peut être une activité joyeuse et inclusive. bell hooks montre le chemin. "Lorsque les enseignant.e.s enseignent avec amour, en combinant attention, engagement, connaissances, responsabilité, respect et confiance, nous sommes souvent capables d'entrer dans la classe et d'aller droit au cœur du problème, qui est de savoir quoi faire un jour donné pour créer le meilleur climat d'apprentissage."
Keywords: afro-féminisme; amériques; approches et analyses; cours; cycles supérieurs; fem9000; féminisme afroaméricain; inégalités; pédagogie; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; états-unis

Logiques de genre dans l'enseignement associatif : carrières et pratiques militantes dans des associations revendicatives, 2013 - Rétif, Sophie (Dalloz, 2013)
Thèse pour le doctorat en science politique de l’Institut d’Etudes Politiques de Paris présentée et soutenue sous le titre Genre et engagement associatif. Carrières et pratiques militantes dans six associations françaises et portugaises. Tout espace social où s’organisent des rapports de genre apporte à leur structuration sa contribution propre. Cela veut dire qu’il faut ici prendre au sérieux les idéologies, les croyances comme affectant les anticipations et comportements ouverts aux femmes et hommes au sein des associations. (…) Ici encore, avec ce confort de lecture qui consiste à offrir des analyses stimulantes et bien construites sans les hérisser d’une envahissante signalétique théorique, Sophie Rétif met en oeuvre les fondamentaux d’une analyse de genre intelligente.
Keywords: activisme; approches et analyses; cours; cycles supérieurs; discipline; europe; fem7000; france; idéologie; inégalités; justice sociale; militance; mouvements sociaux; organisations féministes; portugal; rapports de domination; rapports sociaux de sexe; recherche comparative; recherche en milieux de pratique; reproduction sociale; régions géographiques; science politique; science politique et droit; systèmes d'oppressions; thématiques; travail; étude de cas; étude qualitative

Epistemic Justice as a Virtue of Social Institutions - Anderson, Elizabeth (Social Epistemology, 2012)
In Epistemic injustice, Miranda Fricker makes a tremendous contribution to theorizing the intersection of social epistemology with theories of justice. Theories of justice often take as their object of assessment either interpersonal transactions (specific exchanges between persons) or particular institutions. They may also take a more comprehensive perspective in assessing systems of institutions. This systemic perspective may enable control of the cumulative effects of millions of individual transactions that cannot be controlled at the individual or institutional levels. This is true not only with respect to the overall distribution of such goods as income and wealth, but also with respect to the goods of testimonial and hermeneutical justice. Cognitive biases that may be difficult for even epistemically virtuous individuals to correct on their own may be more susceptible to correction if we focus on the principles that should govern our systems of testimonial gathering and assessment. Hence, while Fricker’s focus on individual epistemic virtue is important, we also need to consider what epistemic justice as a virtue of social systems would require. My paper will indicate some directions forward on this front, focusing on the need for integration of diverse institutions and persons engaged in inquiry.
Keywords: approches et analyses; biais cognitifs; capitalisme; cours; cycles supérieurs; discipline; droits des personnes; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; inégalités; justice épistémique; philosophie; sciences humaines; systèmes d'oppressions; thématiques; violences; éthique

Tracking Epistemic Violence, Tracking Practices of Silencing - Dotson, Kristie (Hypatia, 2011)
oo often, identifying practices of silencing is a seemingly impossible exercise. Here I claim that attempting to give a conceptual reading of the epistemic violence present when silencing occurs can help distinguish the different ways members of oppressed groups are silenced with respect to testimony. I offer an account of epistemic violence as the failure, owing to pernicious ignorance, of hearers to meet the vulnerabilities of speakers in linguistic exchanges. Ultimately, I illustrate that by focusing on the ways in which hearers fail to meet speaker dependency in a linguistic exchange, efforts can be made to demarcate the different types of silencing people face when attempting to testify from oppressed positions in society.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem9000; injustices épistémiques; inégalités; justice; philosophie; sciences humaines; silenciation; systèmes d'oppressions; thématiques; témoignage; violences; vulnérabilité; éthique

The Relevance of Credibility Excess in a Proportional View of Epistemic Injustice: Differential Epistemic Authority and the Social Imaginary - Medina, José (Social Epistemology, 2011)
This paper defends a contextualist approach to epistemic injustice according to which instances of such injustice should be looked at as temporally extended phenomena (having developmental and historical trajectories) and socially extended phenomena (being rooted in patterns of social relations). Within this contextualist framework, credibility excesses appear as a form of undeserved epistemic privilege that is crucially relevant for matters of testimonial justice. While drawing on Miranda Fricker's proportional view of epistemic justice, I take issue with its lack of attention to the role that credibility excesses play in testimonial injustices. I depart from Fricker's view of the relation between credibility excesses and credibility deficits, and I offer an alternative account of the contributions that undeserved epistemic privileges make to epistemic injustices. Then, through the detailed analysis of To kill a mockingbird, I elucidate the crucial role played by the social imaginary in creating and sustaining epistemic injustices, developing an analysis of the kind of social blindness produced by an oppressive social imaginary that establishes unjust patterns of credibility excesses and deficits.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; droit; fem9000; histoire et politique; injustices épistémiques; inégalités; justice sociale; philosophie; privilèges; privilèges de crédibilité; science politique et droit; sciences humaines; systèmes d'oppressions; thématiques; éthique

Teaching critical thinking: Practical wisdom - hooks, bell (Routledge, 2010)
Dans une série d'essais courts, accessibles et éclairants, hooks explore les sujets déroutants et parfois controversés que les enseignants et les élèves l'ont invitée à aborder depuis la publication des précédents volumes à succès de sa série Teaching, Teaching to Transgress et Teaching Community . . Les questions sont variées et vastes, allant de la question de savoir si un enseignement significatif peut avoir lieu dans une grande salle de classe à la confrontation des problèmes d'estime de soi. Un professeur, par exemple, a demandé comment les professeures noires peuvent maintenir une autorité positive dans une salle de classe sans être vues à travers le prisme de stéréotypes racistes et sexistes négatifs. Un enseignant a demandé comment gérer les larmes en classe, tandis qu'un autre voulait savoir comment utiliser l'humour comme outil d'apprentissage. Abordant les questions de race, de sexe et de classe dans ce travail, hooks discute de l'équilibre complexe qui nous permet d'enseigner, de valoriser et d'apprendre des œuvres écrites par des auteurs racistes et sexistes. Soulignant l'importance de la lecture, elle insiste sur la primauté de la liberté d'expression, une éducation démocratique de l'alphabétisation. Tout au long de ces essais, elle célèbre le pouvoir transformateur de la pensée critique. C'est un travail intellectuel provocateur, puissant et joyeux. C'est une lecture incontournable pour tous ceux qui s'intéressent à l'éducation aujourd'hui.
Keywords: afro-féminisme; amériques; approches et analyses; cours; cycles supérieurs; discours dominant; fem9000; féminisme afroaméricain; inégalités; pédagogie; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; états-unis

La disqualification sociale : essai sur la nouvelle pauvreté - Paugam, Serge (PUF, 2009)
Ce livre repose sur les résultats d'une enquête sociologique réalisée à Saint-Brieuc (Bretagne) auprès des populations bénéficiaires de l'assistance sociale. Il montre, à partir de l'analyse de trois types de population, comment se constituent les statuts, les identités et les rapports sociaux à la périphérie du marché de l'emploi. Publié d'abord comme thèse de doctorat de l'auteur.
Keywords: 1900-1999; 1980-1989; approches et analyses; assistance sociale; cours; cycles supérieurs; discipline; disqualification sociale; enquête longitudinale; ethnographie; europe; fem7000; france; insertion sociale; inégalités; marginalité; pauvreté; périodes historiques; rapports sociaux; ressource en ligne; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions

Concepts fondamentaux pour les études de genre - Roventa-Frumusani, Daniela (Agence universitaire de la francophonie, 2009)
C'est dans la perspective de l'amélioration du sort de la moitié de l'humanité que nous avons conçu ce lexique fondamental expliquant la genèse et le fonctionnement de la violence, du travail, de l'inégalité conjuguées au féminin, dans l'espoir que les jeunes générations y réfléchiront et agiront en famille, sur le marché du travail, dans l'agora et les médias. Nous espérons que ce regard (sociologique, historique, méthodologique) sur la situation des femmes contribuera à l'approfondissement de la connaissance et compréhension de nombreuses problématiques concernant " le monde des femmes ", ainsi qu'à la dissolution de ce que Pierre Bourdieu appelle la violence symbolique, exercée essentiellement par les voies symboliques de la communication et de la connaissance, ou plus exactement de la méconnaissance qui a transformé l'histoire en nature et l'arbitraire culturel en naturel. Nous avons essayé aussi de tisser des liens entre les champs des recherches produites dans le monde francophone et celui anglophone, liens absolument indispensable dans la société contemporaine mondialisée. Nous estimons que cet ouvrage sera utile à tous ceux / celles interpellées par les grands problèmes du monde contemporain et désireux de participer au changement social. Les philosophes ont interprété le monde, disait Marx, mais l'important c'est de le changer ; et on peut le changer en comprenant le passé et le présent afin de préparer l'avenir.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem7000; genre; histoire; identités LGBTQIA2+; inégalités; patriarcat; sciences humaines; sociologie; systèmes d'oppressions; thématiques; violences

Les coulisses de l'État social : enquête sur les signalements d'enfant en danger - Serre, Delphine (Raisons d'agir, 2009)
Pour expliquer le contexte et les critères de signalement par les professionnels de l'administration sociale d'affaires d'enfants maltraités, D. Serre a mené des entretiens auprès d'assistantes sociales et les a suivies dans leurs différentes activités. Cette enquête révèle ce que représente la catégories d'enfants en danger et ce que l'acte de signaler signifie pour les professionnels.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; enfance; europe; fem7000; france; inégalités; maltraitance; maternité; protection de l'enfance; régions géographiques; sciences humaines; sciences sociales; services sociaux; systèmes d'oppressions; thématiques; travail social; violences

Conceituando Empoderamento na Perspectiva Feminista - Sardenberg, Cecília M B (2006)
Transcription d’une communication au séminaire International : « Trilhas do empoderamento de mulheres », Salvador da Bahia, 5-10 juin 2006.
Keywords: amérique latine; amériques; anthropologie; approches et analyses; brésil; cours; cycles supérieurs; discipline; empowerment; fem7000; inégalités; justice sociale; militance; mouvements sociaux; patriarcat; pratiques féministes; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sofia; systèmes d'oppressions; thématiques; épistémologie

Quand les femmes s'en mêlent : genre et pouvoir - Bard, Christine; Baudelot, Christian; Mossuz-Lavau, Janine (Éditions de La Martinière, 2004)
C'est dans les années 1970 que des anthropologues féministes américaines, réfléchissant aux rapports de pouvoir entre hommes et femmes, ont intronisé le mot " genre " : elles faisaient ainsi référence au rôle social des uns et des autres, par opposition au sexe biologique, pour montrer que la place des femmes et des hommes dans la société est avant tout le produit d'une culture. Simone de Beauvoir l'avait déjà dit avec d'autres mots : " On ne naît pas femme, on le devient. " Au moment même où la hiérarchie traditionnelle des sexes était remise en cause, des chercheuses et des chercheurs en sciences sociales reprirent le concept et sapèrent ainsi l'idée que la domination masculine était " naturelle ". Depuis, le principe de l'égalité entre les droits de l'homme et les droits de la femme a fait son chemin. Mais le principe est-il devenu réalité ? Les historien(ne)s, sociologues, politologues que réunit ce livre font un bilan : quand les femmes s'en mêlent, qu'il s'agisse de la vie publique ou de la vie privée, les inégalités demeurent, ou se transforment, comme si un pas en avant sur la voie de l'égalité déclenchait deux pas en arrière. En politique, parité ne signifie toujours pas égalité. Dans le monde du travail, les femmes sont plus frappées par le chômage, alors qu'elles sont plus nombreuses à l'Université. Pourquoi tant de femmes qui veulent accéder à des postes de responsabilité échouent-elles à traverser le plafond de verre ? Et pourquoi du sexisme ordinaire au viol, les violences à l'encontre des femmes sont-elles si fréquentes ?
Keywords: approches et analyses; cours; cycles supérieurs; fem9000; genre; identités LGBTQIA2+; interdisciplinarité; inégalités; systèmes d'oppressions; thématiques; travail; violences

La grande arnaque : sexualité des femmes et échange économico-sexuel - Tabet, Paola (L'Harmattan, 2004)
Dans la majorité des sociétés connues, la sexualité apparaît comme un échange asymétrique et non réciproque entre hommes et femmes, une compensation masculine pour une prestation féminine, un paiement qui peut revêtir les formes les plus variées en échange d'une sexualité transformée en service. Comment se fait-il que les hommes, même plongés dans les situations les plus misérables, peuvent se payer le service sexuel d'une femme - alors que non seulement les femmes n'ont pas, sauf exception, cette possibilité mais de plus n' ont même pas droit à leur propre sexualité ?
Keywords: EDI; approches et analyses; cours; cycles supérieurs; discipline; division sexuelle du travail; ethnologie; fem1000; fem7000; inégalités; lit3220; premier cycle; rapports sociaux de sexe; sciences; sciences humaines; sexualité; systèmes d'oppressions; thématiques; épistémologie

Regards de femmes sur la globalisation : approches critiques - Bisilliat, Jeanne (Karthala, 2003)
L'une des originalités de cet ouvrage est d'offrir au public francophone une pensée féministe critique, encore peu connue en France, des institutions internationales (Nations Unies, Banque mondiale, Fonds monétaire international) et de la dangereuse récupération des pauvres et des femmes à laquelle elles se livrent. Quels que soient leur faiblesse et leur dénuement, tous devraient devenir des consommateurs et tous les moyens, parés de l'infinie bonne conscience du capitalisme, sont bons pour arriver à ce résultat convoité. Dégradante convoitise qui se cache, trop souvent avec l'aide des Nations Unies, sous le vocable de l'aide au " développement ". C'est là un des redoutables aspects de la mondialisation ; il réside dans un paradoxe tout aussi redoutable : la prolifération d'un discours multiforme mais univoque, diffusé sans répit selon de multiples modalités de communication, ce qui efface son sens et le lisse jusqu'à le rendre translucide. Autosatisfaction sémantique; mithridatisation par la monotonie. D'autres contributions montrent en contrepoint l'inscription factuelle des dénonciations générales. Les exemples fournis auraient pu être plus nombreux mais il nous a semblé suffisant de marquer quelques liens parmi d'autres.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; discours dominant; fem9000; inégalités; sciences humaines; sociologie; systèmes d'oppressions